PROSPEK USAHA INOVASI PRODUK KAPSUL BAWANG HITAM SEBAGAI SUMBER ANTIOKSIDAN PENANGKAL RADIKAL DALAM MENGHADAPI PANDEMI - Ratih Apri Utami; Anarofida Anarofida; Meihilda Dona Pratiwi; Ajeng Gendis Purborini; Dhea Karunia Putri; Rofiu Sisil Annisa (Politeknik Negeri Semarang, 2021)
In the era of the Covid-19 pandemic, an immune booster is needed that can maintain a person's immune system to become more immune to the corona virus. Therefore the product